Code-mixing among Students of English Literature 2009 in Universitas Indonesia - Ditya, Andari (Paradigma: Jurnal Kajian Budaya, 2013)
People today are more globalized than before, and most of them are now able to speak more than one language. It also happens among the English Literature students 2009 in Universitas Indonesia who are able to speak English in their daily conversation. This may lead to the phenomenon called code- mixing. However, this code-mixing focuses more on written communication in their social media’s status. There are two major points that this paper attempts to make. First, the description of code- mixing itself according to the theory given by Wardhaugh (1986) and Hoffman (1991) and how it can be reflected into daily communication, especially in written communication. Second, the reasons why those students tend to do code-mixing in their written communication. This will be supported by all the captured-pictures of their status in their social media. Using this theory, it attempts to dig deeper and analyze the students’ reasons forusing code-mixing in their social media’ status and what words are commonly used in certain topics of conversation.